2013
DOI: 10.1142/s0192415x13500560
|View full text |Cite
|
Sign up to set email alerts
|

Ligusticum chuanxiong Prevents Ovariectomy-Induced Liver and Vascular Damage in Rats

Abstract: Post-menopause, there is an increase in body weight, visceral adiposity, and risk of developing non-alcoholic fatty liver disease (NAFLD), which leads to various cardiovascular diseases (CVDs). Some natural products have proven useful for counteracting the detrimental effects of menopause. The rhizome of Ligusticum chuanxiong Hort. (LC) is a well-known medicinal herb widely used in Chinese communities for the treatment of CVDs. The hepatic and vascular protective effects of LC ethanolic extract under postmenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Based on the current finding, OVX rats had high lipid peroxidation in the liver, an increase in MDA and NO levels, and a decrease in SOD and GSH‐PX. Such findings suggest that ovariectomy causes oxidative stress in the liver, thereby aligning with previous findings (Jeong et al, ; Li et al, ). Estrogen could decrease ROS levels by increasing the production of SOD and GSH‐PX (Oge, Sezer, Özgönül, Bayraktar, & Sözmen, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the current finding, OVX rats had high lipid peroxidation in the liver, an increase in MDA and NO levels, and a decrease in SOD and GSH‐PX. Such findings suggest that ovariectomy causes oxidative stress in the liver, thereby aligning with previous findings (Jeong et al, ; Li et al, ). Estrogen could decrease ROS levels by increasing the production of SOD and GSH‐PX (Oge, Sezer, Özgönül, Bayraktar, & Sözmen, ).…”
Section: Discussionsupporting
confidence: 92%
“…This experiment was conducted according to a previous study (Li, Wu, & Yang, ). A Hitachi 7020 automatic biochemistry analyzer (Hitachi Co. Ltd., Japan) was used to determine the content of serum total cholesterol (TC) (Cat No: 07485/00003709), TG (Cat No: 07420/00003568), low‐density lipoprotein cholesterol (LDL‐C) (Cat No: 23748/00003964), high‐density lipoprotein cholesterol (HDL‐C) (Cat No: 23759/00003933), alanine transaminase (ALT) (Cat No: 07495/00003783), and aspartate transaminase (AST) (Cat No: 07496/00003763) in blood samples using specific kits from Shenergy‐DiaSys Diagnostic System Co., Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some TCMs such as PR [15] , [16] and CR [17] , [18] have been suggested to possess a range of pharmaceutical effects, including anti-cancer, cardio-, hepatic- and neuro-protection. It has been reported that several substances in PR, such as puerarin [13] , daidzin [19] , [20] , daidzein [21] , [22] , genistein [23] , [24] and formononetin [25] , [26] , and one compound (ligustilide [27] ) in CR could remedy mitochondrial functions to exert their pharmacological efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Natural products with hepatoprotective activity have been applied to protect various liver disorders (Gou et al, 2013;Li et al, 2013), however only few of them have been proven for hepatoprotective activities against ALI (Adewusi and Afolayan, 2010). Silymarin is the most popular drug against ALI despite of a controversy about its effect.…”
Section: Kaempferol Against Ali 11mentioning
confidence: 99%